100 Inventions That Made History Brilliant Breakthroughs That Shaped Our World - Turner, Tracey; Challoner, Jack; Gifford, Clive; Mills, Andrea (London Dorling Kindersley Limited, 2010)
Discover the inventions that helped shape the world we know today 100 Inventions That Made History is no ordinary history book. Take a look at the trailblazing inventions that have advanced technology and transformed the way we live, as well as the gadgets and gizmos we couldn't live without! From cars and planes to the printing press and television, from the light bulb to antibiotics, computer games to jeans, this top 100 comes from all over the world, taking in all types of inventions. Each profile explores key inventions in depth, while gallery spreads bring together the major inventions in a particular area. Plus, the inventions are put into historical context with "It couldn't have been done without..." and "It paved the way for..." panels. Take a seat and view the brilliant breakthroughs that have changed our world with engaging graphics and unusual facts in 100 Inventions That Made History
World arround us (Inventions)
2
Keywords: Inventions